2010
DOI: 10.1136/ard.2009.126573
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence for the management of rheumatoid arthritis with biological disease-modifying antirheumatic drugs: a systematic literature review informing the EULAR recommendations for the management of RA

Abstract: There is good evidence for the efficacy of biological agents in patients with RA. Safety data confirm an increased risk of bacterial infection and TB with TNFi compared with conventional DMARDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
217
0
23

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(245 citation statements)
references
References 89 publications
(112 reference statements)
5
217
0
23
Order By: Relevance
“…Randomized controlled clinical trials have established that the addition of anti-tumor necrosis factor (TNF) agents to MTX therapy in patients with an inadequate response to MTX results in significant improvements in clinical, radiographic, and functional outcomes 4,5,6,7,8,9,10,11 . Current recommendations for patients with poor prognostic factors suggest treatment with MTX for 3 to 6 months before considering the addition of biologic DMARD therapy 12 , but some rheumatologists continue MTX for longer periods before considering the addition of biologic therapy 13,14 .…”
mentioning
confidence: 99%
“…Randomized controlled clinical trials have established that the addition of anti-tumor necrosis factor (TNF) agents to MTX therapy in patients with an inadequate response to MTX results in significant improvements in clinical, radiographic, and functional outcomes 4,5,6,7,8,9,10,11 . Current recommendations for patients with poor prognostic factors suggest treatment with MTX for 3 to 6 months before considering the addition of biologic DMARD therapy 12 , but some rheumatologists continue MTX for longer periods before considering the addition of biologic therapy 13,14 .…”
mentioning
confidence: 99%
“…La méta-analyse de Leombruno et al [37] n'a pas non plus mis en évidence de différence significative entre les patients sous anti-TNF et les patients sous nbDMARDs. Plusieurs études [31,38,39] ont conclu à une augmentation du risque infectieux au cours des six premiers mois de traitement, le temps que la maladie inflammatoire soit stabilisée. La PR représente un risque inhérent d'infection imputé au dysfonctionnement du système immunitaire.…”
Section: Discussionunclassified
“…Multiple studies have demonstrated significant benefits of early treatment with TNF-inhibitors combined with methotrexate (27)(28)(29). Other FDA-approved biologic agents for treating moderate-to-severe RA include abatacept, rituximab, and tocilizumab (30)(31)(32)(33). However, all biologic agents carry an increased risk of infections.…”
Section: Current Biological Therapies For Ramentioning
confidence: 99%